Atmospheric Chemistry and Air Pollution - Jeffrey S. Gaffney; Nancy A. Marley (The Scientific World Journal)
Atmospheric chemistry is an important discipline for understanding air pollution and its impacts. This mini-review gives a brief history of air pollution and presents an overview of some of the basic photochemistry involved in the production of ozone and other oxidants in the atmosphere. Urban air quality issues are reviewed with a specific focus on ozone and other oxidants, primary and secondary aerosols, alternative fuels, and the potential for chlorine releases to amplify oxidant chemistry in industrial areas. Regional air pollution issues such as acid rain, long-range transport of aerosols and visibility loss, and the connections of aerosols to ozone and peroxyacetyl nitrate chemistry are examined. Finally, the potential impacts of air pollutants on the global-scale radiative balances of gases and aerosols are discussed briefly.